2009
DOI: 10.2187/bss.23.203
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria for Space Agriculture on Mars

Abstract: The growth of terrestrial cyanobacterium, Nostoc sp., on the Martian Regolith Simulant (MRS) and its vacuum tolerance were examined in relevance of our challenges to inhabit M a r s . T h e via b ilit y of t h e cyanob a c te ria was evaluated by microscopic observation a f t e r s t a i n i n g b y f l u o r e s c e i n d i a c e t a t e (FDA). The general terrestrial cyanobacterial lump collected from the ground showed a significantly high tolerance against exposure to high vacuum environment for more than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Nostoc sp. HK-01 may be suitable to create organic soil from Martian regolith (Arai et al, 2008;Arai, 2009;Oarga, 2009;Verseux et al, 2016). The result indicates that the cyanobacterium can also be used to add nutrition to harsh environments on Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Nostoc sp. HK-01 may be suitable to create organic soil from Martian regolith (Arai et al, 2008;Arai, 2009;Oarga, 2009;Verseux et al, 2016). The result indicates that the cyanobacterium can also be used to add nutrition to harsh environments on Earth.…”
Section: Introductionmentioning
confidence: 99%
“…This simulant was based on the NASA-created JSC Mars-1 regolith simulant built from data from rover missions. In a simulated closed system at 90% of Earth’s atmospheric pressure, growth of the organism was exhibited [ 28 ]. Water was formed from the metabolic reactions and drops were observed on the inside of the glass [ 28 ].…”
Section: Habitat Alsmentioning
confidence: 99%
“…In a simulated closed system at 90% of Earth’s atmospheric pressure, growth of the organism was exhibited [ 28 ]. Water was formed from the metabolic reactions and drops were observed on the inside of the glass [ 28 ]. It was concluded that the Nostoc sp.…”
Section: Habitat Alsmentioning
confidence: 99%
“…Nostoc sp. HK-01 may be able to create organic soil from Martian regolith (Arai et al, 2008;Arai, 2009;Oarga, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HK-01 has not been investigated, although their tolerances to desiccation for 8 months, to 200 mM NaCl stress, and to vacuum (10 -5 Pa) for 2 weeks, have been investigated (Yoshimura et al, , 2012Arai et al, 2008;Arai, 2009). In low Earth orbit, the temperature of a body in space can become extremely high due to solar radiation (1,366 W m -2 ) and no convection.…”
Section: Introductionmentioning
confidence: 99%